Modern economic growth and quality of life: cross sectional and time series evidence - Richard A. Easterlin; Laura Angelescu (Institute for the Study of Labor (IZA), 2007)
To what extent are improvements in quality of life (material living levels, health, education, political and civil rights, happiness, and the like) associated with economic growth? International comparisons of quality of life (QoL) conditions almost always point to a strong positive association with real GDP per capita. Historical experience, however, frequently belies the results of these comparisons. More often than not the timing of various improvements in QoL, material living levels excepted, is different from that in real GDP per capita some indicators preceding, others following. Moreover, the sequence of improvements in various aspects of QoL is not always the same from one part of the world to another. And sometimes, as in the case of happiness and life satisfaction, QoL indicators remain unchanged despite a doubling or more of real GDP per capita. In contrast to the results of simple international point-of-time comparisons, history suggests that improvements in many realms of life are not an automatic result of economic growth.
urn:nbn:de:101:1-20080402198
Keywords: 330; Lebensqualität; Lebenszufriedenheit; Wirtschaftswachstum; Lebensstandard; Welt